The total vertex irregularity strength of symmetric cubic graphs of the Foster's Census - Rika Yanti; Gregory Benedict Tanidi; Suhadi Wido Saputro; Edy Tri Baskoro (Indonesian Journal of Combinatorics, 2022)
Foster (1932) performed a mathematical census for all connected symmetric cubic (trivalent) graphs of order n with n ≤ 512. This census then was continued by Conder et al. (2006) and they obtained the complete list of all connected symmetric cubic graphs with order n ≤ 768. In this paper, we determine the total vertex irregularity strength of such graphs obtained by Foster. As a result, all the values of the total vertex irregularity strengths of the symmetric cubic graphs of order n from Foster census strengthen the conjecture stated by Nurdin, Baskoro, Gaos & Salman (2010), namely ⌈(n+3)/4⌉.